Love and marriage - Cosby, Bill (New York : Doubleday & Company, Inc., 1989)
Provides a humorous look at love and marriage from childhood romance to the institution of marriage.
Part I. Love -- 1. Prescription from Dr. Kinsey -- 2. As the bottles spin -- 3. Did you get any? -- 4. Somebody mop that chapel -- 5. in training for vagrancy -- 6. A fling on the track -- 7 Just baby and me and Coltrane makes three -- 8. Salvation called Camille -- Part II : Marriage -- 9. What did you say a closet is for? -- 10. Your beloved foe -- 11. To love, honor, and drive up the wall -- 12. Till talk do you part -- 13. La difference -- 14. A wing and a prayer -- 15. The promised land
Keywords: LOVE -- ANECDOTES